Process Technology for the Preparation of Multi-Millet-Based Probiotic Biscuit - Arepally, Divyasree (Curtin University, 2024)
The rising popularity of functional food in the diet due to their possible health benefits has driven probiotic food innovation. This PhD study optimizes encapsulation for probiotic powder, develops oleogel-based filling cream, and explores possible ways of developing multi-millet-based probiotic biscuit. The optimized probiotic powder enhanced flowability, cell survival, and thermal stability. Inclusion of probiotics in biscuit filling cream found high cell viability under simulated gastro-intestinal conditions than those directly added to dough and baked.